The Role of Youth in Nation Building: A Hadith Perspective - Mardiyati, Raudatul Himmatil (ASILHA (Asosiasi Ilmu Hadis Indonesia), 2018)
The background of this researchwas by the fact that the role of youth in national development was still low becauseMuslims youth seemslike losing their way, experiencing stagnation of creativity, getting out of their natural rotation, and losing their role models in their lives.At this time many of the Muslims youth are ensnared by the globalization virus that eliminates the extraordinary youth figure throughout the history of Islam. Even that disseminated artists who are product of temporal world. The impact of losing role modelsis can be imitating bad Western culture.Start from hedonism, wasting money, dating. This research find the results if want to build the people and seek the return of the glory of Islam, Muslim youth will take that role. Youth's active role as a moral force is realized by developing ethical and moral aspects in acting on every dimension of youth life, strengthening faith and piety and mental-spiritual endurance, and increasing legal awareness. One day glory ofislam was an accumulative work between generations, the triumph of Muslims will never stand only with the blood of one young man, not only with the tears of a young man, not only with the idea of one young man, therefore what is needed by Muslims in the future was not a young man, but a youth union and movement that initiates the unity of Muslims